2019
DOI: 10.1186/s12998-018-0229-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study for clinical signs of MODIC changes in patients with low-back pain in the Netherlands armed forces

Abstract: Background Magnetic resonance imaging (MRI) is being used extensively in the search for pathoanatomical factors contributing to low back pain (LBP) such as Modic changes (MC). However, it remains unclear whether clinical findings can identify patients with MC. The purpose of this explorative study was to assess the predictive value of six clinical tests and three questionnaires commonly used with patients with low-back pain (LBP) on the presence of Modic changes (MC). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…These results suggest that one cannot distinguish patients with type 1 MCs from patients with type 2 MCs only based on clinical symptoms and signs. Our findings are in accordance with a study on Dutch military personnel which reported no differences in various clinical tests between type 1 and 2 MCs [48] and a study which did not report any difference in duration of symptoms between type 1 and type 2 MCs in hospitalized patients [11].…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that one cannot distinguish patients with type 1 MCs from patients with type 2 MCs only based on clinical symptoms and signs. Our findings are in accordance with a study on Dutch military personnel which reported no differences in various clinical tests between type 1 and 2 MCs [48] and a study which did not report any difference in duration of symptoms between type 1 and type 2 MCs in hospitalized patients [11].…”
Section: Discussionsupporting
confidence: 93%
“…We do recognise that having published their review protocol in Prospero they had limited freedom to do so. Unfortunately, Herlin et al is often being inappropriately cited as demonstrating no association between LBP and MC without acknowledging its limitations [30][31][32][33][34][35][36][37][38], but others do cite it in a more appropriate nuanced way [23,[39][40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Papers citing Herlin et al were identified using Pub-Med [23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The literature was searched through PubMed with the keywords "MRI (back pain) association Modic" restricted to the last 5 years and identified 135 articles.…”
Section: Methodsmentioning
confidence: 99%
“…DWI has been successful in differentiating type 1 MC degeneration from vertebral discitis or osteomyelitis. 43 Similarly, x-rays can be helpful in differentiating MC from other abnormalities such as spondyloarthropathy. 11 Laboratory tests, including erythrocyte sedimentation rate/C-reactive protein, and complete blood count, can exclude alternative diagnoses.…”
Section: Mc: Presentation and Diagnosismentioning
confidence: 99%
“…DWI measures underlying pathology through restricted molecular diffusion of tissue water molecules. DWI has been successful in differentiating type 1 MC degeneration from vertebral discitis or osteomyelitis 43. Similarly, x-rays can be helpful in differentiating MC from other abnormalities such as spondyloarthropathy 11.…”
Section: Mc: Presentation and Diagnosismentioning
confidence: 99%